2010
DOI: 10.1111/j.1574-6968.2010.02165.x
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated methanogenesis from aliphatic and aromatic hydrocarbons under iron- and sulfate-reducing conditions

Abstract: The impact of four electron acceptors on hydrocarbon-induced methanogenesis was studied. Methanogenesis from residual hydrocarbons may enhance the exploitation of oil reservoirs and may improve bioremediation. The conditions to drive the rate-limiting first hydrocarbon-oxidizing steps for the conversion of hydrocarbons into methanogenic substrates are crucial. Thus, the electron acceptors ferrihydrite, manganese dioxide, nitrate or sulfate were added to sediment microcosms acquired from two brackish water loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 60 publications
(79 reference statements)
5
41
0
Order By: Relevance
“…Dolfing et al [2009] have demonstrated that PAH metabolism coupled with methane production is thermodynamically feasible. Furthermore, microcosm experiments successfully showed the degradation of naphthalene, phenanthrene or methylnaphthalene under methanogenic conditions [Berdugo-Clavijo et al, 2012;Chang et al, 2006;Christensen et al, 2004;Maillacheruvu and Pathan, 2009;Siegert et al, 2011].…”
Section: Pah Degradation With Ferric Iron As Electron Acceptormentioning
confidence: 99%
“…Dolfing et al [2009] have demonstrated that PAH metabolism coupled with methane production is thermodynamically feasible. Furthermore, microcosm experiments successfully showed the degradation of naphthalene, phenanthrene or methylnaphthalene under methanogenic conditions [Berdugo-Clavijo et al, 2012;Chang et al, 2006;Christensen et al, 2004;Maillacheruvu and Pathan, 2009;Siegert et al, 2011].…”
Section: Pah Degradation With Ferric Iron As Electron Acceptormentioning
confidence: 99%
“…In the last decades, however, the topic has regained scientific attention and many studies attempting to explain the mechanistic aspects and to identify key microorganisms involved have been conducted. The conversion of hydrocarbons to methane has been extensively demonstrated in laboratory experiments ( table 2 ) Feisthauer et al, 2010;Gray et al, 2011;Gründger et al, 2015;Jiménez et al, 2012;Jones et al, 2008;Siegert et al, 2011;Tan et al, 2013;Wang et al, 2011;Zengler et al, 1999].…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Generally, it has been considered that SO 4 2-concentrations above 50 μM cause methanogens to be outcompeted by sulfate-reducing bacteria using the same substrates more efficiently, whereas lower concentrations could even enhance methanogenesis [Siegert et al, 2011].…”
Section: Methanogenic Hydrocarbon Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…Biodegradation of petroleum hydrocarbons under iron-and manganese reducing conditions has been noted primarily for low molecular weight aromatic compounds. This includes benzene (Kunapuli et al, 2008), toluene Edwards and Grbic-Galic, 1994;Langenhoff et al, 1997;Lee et al, 2012), ethylbenzene (Siegert et al, 2011) and o-xylene (Edwards and Grbic-Galic, 1994) as well as phenol (Lovley et al, 1989), naphthalene and also liquid alkanes (Siegert et al, 2011).…”
Section: Naturally Mediated Extracellular Electron Transfermentioning
confidence: 99%